Organic online - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
A new Website dedicated to organic farming was launched by CABI Publishing in May 2001, with more than 100,000 abstracts on organic research, weekly news stories, research papers, and books. Some information, such as news headlines, jobs,...